Increasing the Motivation and Learning Outcomes of Students through the Application of the Problem Based Learning Model in Learning Physics - Desta Velly (Pascasarjana, Mataram University, 2021)
The results of the learning test show that almost more than half of the students have not been able to solve the questions well, so learning improvements or innovations are needed. Problem based learning is one of the recommended learning models in the implementation of the 2013 curriculum because this model is proven to be able to stimulate higher-order thinking skills by designing problems in real contexts. The purpose of this action research is to improve learning outcomes and student motivation in the application of the Problem Based Learning model in learning physics. The subjects of this study were students of class XI MIPA 2, Public Senior High School 12 Pekanbaru. This research is a classroom action research conducted in 2 cycles. The results of this study obtained test data on the learning outcomes of students in cycle I with absorption of 75.25%, in cycle II absorption of 81.29%, motivation of students in learning cycle I and cycle II in good categories.